The disease suppression of soybean (var. Grobogan) by the implementation of Bacillus subtilis strain CR.9 antifungal compounds nanoemulsion - Rury Eryna Putri; Nisa Rachmania Mubarik; Laksmi Ambarsari; Aris Tri Wahyudi (Journal of the Saudi Society of Agricultural Sciences, 2023)
Bio-based fungicides with nanotechnology delivery systems employing bacterial products, such as antifungal compounds, could be an alternative substitution for synthetic fungicides. Antifungal activity of extract from B. subtilis strain CR.9 and its nanoemulsion formula using medium-chain triglycerides (MCT) and Tween-80 was evaluated in vitro and in planta effectiveness against Fusarium oxysporum f. sp. glycines associated with soybean plants. For this purpose, the antifungal compounds from bacterial culture were recovered using ethyl acetate as an organic solvent. The fungitoxic activity of antifungal compounds strains CR.9 demonstrated fungal growth inhibition at 394.12 µg/mL (IC50), 250 µg/mL (MICEE), and 100 µg/mL (MICnanoemulsion), respectively. The EtOAc extract (EE)-nanoemulsion formula developed with a ratio of 2:1 (MCT: Tween-80) showed homogenous size and stability for 25 days without creaming, sedimentation, or separate layers. Moreover, seedlings treatment and soil amendment of EE-nanoemulsion performed high efficacy in suppressing wilt and in agreement with commercial fungicide, Dithane M−45. Overall, the antifungal properties of strain CR.9 may have potency as a bio-based fungicide in plant diseases biocontrol strategy.